2017
DOI: 10.1021/acs.jctc.7b00464
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Molecular Dynamics–Rosetta Membrane Protein Structure Refinement Guided by Cryo-EM Densities

Abstract: Knowing atomistic details of proteins is essential not only for the understanding of protein function but also for the development of drugs. Experimental methods such as X-ray crystallography, NMR and cryo-EM are the preferred form of protein structure determination and have achieved great success over the last decades. Computational methods may be an alternative when experimental techniques fail. However, computational methods are severely limited when it comes to predicting larger macromolecule structures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 96 publications
1
26
0
Order By: Relevance
“…We have previously shown that the correlation between experimentally determined PFs and residue neighbor count can be exploited as a Rosetta scoring term to improve protein structure prediction 20 . In addition, computational protein structure prediction guided with sparse experimental data has been successfully implemented for a wide range of experimental data 21 27 . Our previous HRPF modeling work, however, relied on static protein structures.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the correlation between experimentally determined PFs and residue neighbor count can be exploited as a Rosetta scoring term to improve protein structure prediction 20 . In addition, computational protein structure prediction guided with sparse experimental data has been successfully implemented for a wide range of experimental data 21 27 . Our previous HRPF modeling work, however, relied on static protein structures.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental methods, such as cryo-electron microscopy (cryo-EM), [1][2][3][4][5][6] X-ray crystallography, [7][8][9][10][11][12][13][14] and nuclear magnetic resonance (NMR) [15][16][17][18][19][20][21] spectroscopy have been widely used together with other methods, such as small-angle X-ray scattering, to study the conformations of peptides and proteins. However, due to the sample preparation requirements and artefacts of crystallisation, the structures observed using X-ray techniques do not adequately reflect the relevant biological conformations of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the low (~10–25 Å) or medium-resolution (~4–10 Å) density maps, the backbone of the protein and the atomic information cannot be directly achieved from the cryo-EM maps. This limitation has motivated the development of many computational methods that use the medium-resolution cryo-EM map to collect protein structural information [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In the cryo-EM modeling pipeline, some major steps should be handled, such as extracting the secondary structure elements on a cryo-EM density map and matching them to a sequence/model, the placement of SSEs, building an atomic structure, and structure optimization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a high-resolution structure for an insufficient resolution cryo-EM map, the fitting methods, which are categorized into flexible and rigid-body fitting, could be utilized to derive the atomic structure from the cryo-EM map [ 9 , 12 , 14 , 17 ]. Early studies have concentrated on searching for the optimal position and orientation of a protein’s secondary structure components with the best overlaps with the SSEs extracted from a cryo-EM density map [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%